Reduced cortical somatostatin gene expression in a rat model of maternal immune activation. (December 2019) - Duchatel, Ryan J.; Harms, Lauren R.; Meehan, Crystal L.; Michie, Patricia T.; Bigland, Mark J.; Smith, Doug W.; Jobling, Phillip; Hodgson, Deborah M.; Tooney, Paul A.
Highlights: Maternal immune activation decreased cortical SST mRNA in the adult offspring. No change in cortical GAD mRNA in adult offspring exposed to maternal immune activation. Maternal immune activation did not alter GAD-positive white matter neuron density. Maternal immune activation models some but not all schizophrenia-like interneuron pathologies. Abstract: Alterations in GABAergic interneurons and glutamic acid decarboxylase (GAD) are observed in the brains of people with schizophrenia. Studies also show increased density of interstitial white matter neurons (IWMN), including those containing GAD and somatostatin (SST) in the brain in schizophrenia. Maternal immune activation can be modelled in rodents to investigate the relationship between prenatal exposure to infections and increased risk of developing schizophrenia. We reported that maternal immune activation induced an increase in density of somatostatin-positive IWMN in the adult rat offspring. Here we hypothesised that maternal immune activation induced in pregnant rats by polyinosinic:polycytidylic acid would alter SST and GAD gene expression as well as increase the density of GAD-positive IWMNs in the adult offspring. SST gene expression was significantly reduced in the cingulate cortex of adult offspring exposed to late gestation maternal immune activation. There was no change in cortical GAD gene expression nor GAD-positive IWMN density in adults rats exposed to maternal immune activation at either early or late gestation. This suggests that our model of maternal immune activation induced by prenatal exposure of rats to polyinosinic:polycytidylic acid during late gestation is able to recapitulate changes in SST but not other GABAergic neuropathologies observed in schizophrenia.